The diagnostic accuracy of contemporary ECG interpretation criteria in risk stratification of master athletes - Halasz, Geza; Capelli, Bruno; Crispino, Simone Pasquale; Segreti, Andrea; Mistrulli, Raffaella; Andreoli, Federico; Ferrera, Armando; Perone, Francesco; Villa, Michele; Cassina, Tiziano; Biasini, Vincenzo; Grigioni, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLimited data are available on the diagnostic performance of contemporary ECG interpretation criteria in master athletes (aged over 35 years). This study aimed to describe ECG findings and compare the diagnostic accuracy of the 2017 International, 2010 ESC, and 2013 Seattle criteria in identifying high-risk cardiovascular conditions in a cohort of competitive master athletes.MethodsWe included 506 consecutive Caucasian master athletes (mean age, 47.9 ± 8.7 years; 85.6% male) who underwent ECG-based preparticipation screening. ECGs were retrospectively interpreted according to the three criteria. Transthoracic echocardiography was included to calculate sensitivity and specificity.ResultsThirteen athletes (2.5%) were diagnosed with a condition potentially related to sudden cardiac death (SCD), including severe aortic regurgitation (n = 1), Type 1 Brugada pattern (n = 1), chronic coronary syndromes (n = 4), dilated cardiomyopathy (DCM) (n = 3), aortic dilation (n = 3), and moderate aortic stenosis (n = 1). Diagnostic accuracy for conditions at risk of SCD was 0.73 for International, 0.81 for Seattle, and 0.77 for ESC criteria. Seattle demonstrated a significantly higher AUC than the International criteria (p = 0.0032). The International criteria failed to identify two athletes with DCM and left axis deviation, while no significant structural abnormalities were found in athletes with complete right bundle branch block (RBBB). The most common ECG abnormalities were left axis deviation (7.1%), left atrial enlargement (4.2%), and T-wave inversion (3%). A prolonged QT interval was diagnosed in 5.7% according to ESC criteria but in only one athlete under the International and Seattle criteria.ConclusionThe Seattle criteria demonstrated the highest overall accuracy, with significantly better discriminative performance than the International criteria, and a lower false-positive rate compared with the ESC criteria. These findings support the use of the Seattle criteria as part of a comprehensive screening strategy in master athletes.